Understanding the motivations for keeping wild birds in the semi-arid region of Brazil - Wallisson Sylas Luna de Oliveira; Sérgio de Faria Lopes; Rômulo Romeu Nóbrega Alves (BMC, 2018)
Abstract Background Birds are kept as pets around the world, and bird-keeping is an ancient and widespread practice, constituting one of the main reasons for the decline of some species. In the semi-arid region of Brazil, this practice is very common and continues despite being designated as illegal in recent decades. This study aimed to identify the species and families of songbirds used as pets in the semi-arid region of Brazil, characterize the maintenance of the exploited species in captivity, and evaluate the sociocultural context associated with this practice. Methods Data were collected from a total of 62 wild bird-keepers in the study area through interviews using semi-structured forms and informal conversations. Results A total of 34 bird species are bred as pets in the study area. Thraupidae was the most represented family in this study followed by Icteridae, and together, these families accounted for 61.7% of the local specimens. As reported by the respondents, birds are acquired by capturing them in rural areas or through local and regional markets. The number of species identified by the respondents did not differ according to respondent income, educational level, or age (p > 0.05). Maintaining these birds in cages includes some care, such as providing feed, medicine, and in some cases, training to improve their song or to learn songs from other species. The species with the highest use values (UVs) were Sporophila albogularis (UV = 0.83), Paroaria dominicana (0.82), and Sporophila nigricollis (0.79), indicating their importance as wild animal pets. Conclusion The birds reported in this study have strong cultural importance and high economic value for the people involved in bird-keeping. In this sense, ethnoornithological studies are fundamentally important since they can provide basic information to inform plans and actions to promote the conservation and sustainable management of local avifauna, including the essential element of environmental education strategies.